Cross-layer transmission design in a class of delay-aware two-user interference networks. (2018) - Li, Muhu; Wang, Ping; Wang, Chao; Liu, Fuqiang; Ji, Yusheng
This paper investigates the transmission design problem in a class of two-user interference networks where each source sends two types of delay-sensitive message to its destination. The first type is generated periodically with a fixed rate and is desired to be delivered immediately with sufficiently high reliability. The second type, generated randomly, can be placed in queues but the average queueing delay should be finite. Each user applies point-to-point Gaussian random codes to transmit information, using constrained instantaneous and average powers. We utilise the Lyapunov optimisation theory to construct a cross-layer transmission strategy, which can adapt to both the channel state information (CSI) at the physical layer and the queue state information at the media access control layer. Our results show that the proposed strategy can achieve a better tradeoff among power consumption, transmission reliability, and queueing delay, compared with the conventional CSI-based transmission design.